A study of metastatic lesions of cervical lymphadenopathy by fine needle aspiration cytology - Jethwani, Deepa; Bhalara, Rohit; Dhruv, Gauravi (International Journal of Research in Medical Sciences, 2017)
Background: cervical lymphadenopathy is a common clinical presentation in many diseases. Metastatic lymphadenopathy is common in old age group patient. FNAC is simple, cost effective, reliable and rapid method for diagnosis of metastatis in cervical lymphnodes. FNAC not only give the diagnosis but also give the clue regarding the origin of primary tumor. Methods: Total 144 cases of metastatic lesions of cervical lymphnode were studied from Aug.13 to July 14 by FNAC in cytology section of pathology department in P.D.U. medical college, Rajkot, (Gujarat) India. Result: Squamous cell carcinoma was the most common metastatic lesions of cervical lymphnode comprising (75 %). Metastatic lesions of cervical lymphnode occur more commonly after age of 40 years and more common in male. In anterior cervical lymphnodes, level I and II lymphnodes usually involved where primary was in mouth – buccal mucosa,tongue and level V lymphnodes (supraclavivular lymphnode) involved where primary was in lung. Conclusion: FNAC is a cost effective, reliable, rapid and inexpensive method for diagnosis of lymphadenopathy. Cytology of Metastatic lesions in cervical lymph nodes gives clue to nature & origin of tumors.